Feasibility Study on Use of Cellular Concrete for Air Convection Embankment on Permafrost Foundations in Fairbanks, Alaska - Wu, Hanli; Liu, Jenny; Zhang, Xiong (Transportation Geotechnics, 2020)
The crushed-rock air convection embankment (ACE) is an excellent technique to protect the permafrost from thawing in road construction in cold regions due to its superb cooling effect in winter and excellent thermal resistance performance in summer. However, the desired materials needed for ACE are not readily available, which prevents its extensive use in Alaska. To overcome the limitation (shortage of suitable crushed rocks) of traditional ACE and further improve the cooling effect of ACE, this study investigated the feasibility of using cellular concrete as an alternative material for ACE in cold regions. The finite element method was used to predict the heat transfer patterns of the sand/gravel embankment, the crushed-rock ACE, and the cellular concrete ACE. The results of the present study showed that the cooling performance of both the cellular concrete ACE and the crushed-rock ACE was superior to the conventional sand/gravel embankment. The cellular concrete ACE had better heat insulation property in the summer, and the crushed-rock ACE had stronger natural convection in winter. For the yearly cooling efficiency of the two different ACE techniques, the proposed cellular concrete ACE had a better cooling effect on the foundation soil than the crushed-rock ACE. The results presented in the isotherms and velocity vectors plots for different months of the year also indicated that the thermal conductivity and specific heat capacity of the construction materials had a significant impact on the performance of the ACE. The preliminary cost analyses showed that the cost of the cellular concrete ACE was close to that of the conventional sand/gravel embankment but much lower than that of the crushed-rock ACE.